Designing sustainable pathways for the livestock sector: the example of Atsbi, Ethiopia and Bama, Burkina Faso - Pfeifer, Catherine; Morris, J.; Ensor, J.; Ouédraogo-Koné, S.; Mulatu, D.; Wakeyo, M. (Informa UK Limited, 2021)
Demand for animal sourced food is predicted to double in the upcoming 20 years in Sub-Saharan Africa. This is simultaneously a big opportunity in terms of poverty reduction and a significant threat to the environment. The objective of this paper is to present an approach to co-create a set of viable and acceptable development pathways for the livestock sector that maximizes benefits from increased production, exploits the synergies between livestock and the environment, while minimizing the negative effects. It engages local stakeholders and actors into a computer-assisted participatory process, through which local trade-offs and synergies between livestock production, livelihood benefits and environmental impacts can be explored. Scenarios reached by consensus among local stakeholders challenge the dominant discourse of livestock intensification. They suggest that combining extensive and intensive modes enables increased production of animal sourced food with lower additional pressure on the environment than current production modes. The right combination of extensive and intensive production allows for an efficient use of the local biomass and feed resources, and offers opportunities to improve livelihoods for all stakeholders despite their differing economic circumstances, values and traditions.